2012
DOI: 10.3126/jpn.v2i4.6879
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology findings of mucinous carcinoma of breast: a study of eight cases with histological correlation

Abstract: Background: Pure mucinous carcinoma is a rare histologic type of mammary neoplasm and may exist as mixed mucinous-ductal carcinoma. This study aims to describe fine needle aspiration cytology features of mucinous carcinoma of breast diagnosed in Tribhuvan University Teaching Hospital, Nepal over the period of 2 years and to correlate with histological findings. Materials and Methods:There were a total of 8 cases of mucinous carcinoma of breast, diagnosed on fine needle aspiration cytology in TUTH during the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…[5][6][7] Review of the literature revealed majority of the published literature pertaining to the cytological diagnosis MC are single case reports with only few series available. [6][7][8][9][10] Adhikari et al 7 studied eight cases of MC (5 PMC + 3 MMC) and observed presence of ECM along with single and cluster of tumor cells floating in them and thin walled capillaries as prominent features in five cases of PMC. Three cases of MMC showed in addition to mucin, pleomorphic clusters of tumor cells (as observed in our study).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7] Review of the literature revealed majority of the published literature pertaining to the cytological diagnosis MC are single case reports with only few series available. [6][7][8][9][10] Adhikari et al 7 studied eight cases of MC (5 PMC + 3 MMC) and observed presence of ECM along with single and cluster of tumor cells floating in them and thin walled capillaries as prominent features in five cases of PMC. Three cases of MMC showed in addition to mucin, pleomorphic clusters of tumor cells (as observed in our study).…”
Section: Discussionmentioning
confidence: 99%
“…Cytological diagnosis of PMC is challenging as the features overlap with many benign and malignant lesions. 6,7 Hence, this study was undertaken to document the cytological features of PMC and MMC and to study the clinicopathological parameters associated with PMC and MMC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant nuclear pleomorphism and necrosis, in addition to extracellular mucin suggests mixed MC invasive ductal carcinoma. 5 In general, pure MCs have a favorable prognosis, and the 10-year survival ranges from 80 to 100%. 6 The cytologic features of MC are well established.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be easily repeated if an adequate aspirate is not obtained. The use of core biopsy is the current gold standard but its procedure is more cumber some, expensive, and time consuming as compared to FNA procedure [5,6]. Core biopsy or true cut needle biopsy is not widely used because of its complications, interpretation, and time-consuming results; therefore, palpable breast lesions are mostly diagnosed by screening on the basis of triple assessment only (Physical examination, FNAC, and Mammography) [7].…”
Section: Introductionmentioning
confidence: 99%